2018
DOI: 10.1167/iovs.17-22900
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cortex Activation in Patients With Stargardt Disease

Abstract: Our study, for the first time in the literature, showed stronger PVC activation in STGD1 patients with a more preserved retinal function and macular structure. Furthermore, our study data strongly suggest that the evaluation of neuronal reorganization could be performed by considering only retinal parameters, particularly ERG responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In this study, mfERG was a valuable tool for evaluating the residual function of the retina, and could manifest a correlation with the response of the primary visual cortex in end‐stage glaucoma. This finding was similar to a previous study showing that higher ERG responses were associated with a larger functional cerebral response in subjects with Stargardt disease 43 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, mfERG was a valuable tool for evaluating the residual function of the retina, and could manifest a correlation with the response of the primary visual cortex in end‐stage glaucoma. This finding was similar to a previous study showing that higher ERG responses were associated with a larger functional cerebral response in subjects with Stargardt disease 43 …”
Section: Discussionsupporting
confidence: 93%
“…This finding was similar to a previous study showing that higher ERG responses were associated with a larger functional cerebral response in subjects with Stargardt disease. 43 There were some limitations to this study. Firstly, we did not record the eye movements of the participants.…”
Section: Groupmentioning
confidence: 93%
“…35 This theory is, however, much debated; in fact, other authors have shown that, in patients with late-onset macular degeneration, the persistent activation of foveal corresponding area was due to the activation of close areas (a top-down effect), especially in adults in whom less neuroplasticity phenomena could be expected. 36 To this regard, in our previous study 37 we showed stronger PVC activation in patients with STGD1 with a more preserved retinal function and macular structure, suggesting that the evaluation of neuronal reorganization could be performed only by considering retinal parameters, particularly ERG responses.…”
Section: Discussionmentioning
confidence: 92%
“…In the current experiment, we demonstrated that fMRI can detect signals of spared visual processing with higher sensitivity than other objective and quantitative measures used for standard ophthalmological testing. A recent study on patients with Stargardt disease showed that electrophysiological responses were strongly correlated with activation of the primary visual cortex and concluded that evaluation of neural reorganization can be performed considering ERG responses only 26. However, reliable ERG responses might not be detectable in patients affected by retinal dystrophies at the very late stage,9,11 limiting the diagnostic use of this technique.…”
Section: Discussionmentioning
confidence: 99%